Hendrik Hofmeyr: the harmonic language of a theorist and composer theorist - Crankshaw, Amy Jane (College of Music, 2016)
This dissertation seeks to investigate an aspect of Hendrik Hofmeyr's engagement with music through his theories of harmonic analysis and his use of expanded tonality in his compositions. The purpose of the discipline of music analysis is investigated, and analysis is compared with its sister disciplines to consolidate its vital role in relation to musical study and practice at large. The debate started in the New Musicology in the 1980s is discussed with special reference to the objectives of analysis. The current state of theoretical and analytical study that has emerged since the 1990s is established as a background from which this study takes its cue. Hendrik Hofmeyr's harmonic analytical theories are positioned within the context of this present state of analytical development. Hofmeyr's theories and analytical methods deal with harmonically ambiguous music and expanded tonality. The methods are described in detail in this dissertation, drawing information from Hofmeyr's presentation of his methods of harmonic analysis at the Congress of the Musicological Society of Southern Africa in 2005. The focus then shifts to Hofmeyr's compositional interaction with harmony. Using the methods of Hofmeyr's analytical engagement with harmony, certain complex harmonies in Hofmeyr's Notturno are analysed. The purpose here is to gain a fuller Insight into Hofmeyr's direct compositional interaction with harmony. Hofmeyr's harmonic treatment within the realm of expanded tonality is used as evidence of an individual voice, as something that says,"This is the work of Hendrik Hofmeyr".